SENGKETA PERDAGANGAN ROKOK KRETEK ANTARA INDONESIA DAN AMERIKA SERIKAT DI WORLD TRADE ORGANIZATION - Gregorius Luna Bagaskara; Aluisius Hery Pratono; Firman Rosjadi (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2016)
Since its establishment, the WTO has been issued a lot of policies that are deemed by the WTO Dispute Settlement Body to violate GATT and other WTO agreements. One of the policies is the dispute on clove cigarettes between Indonesia and the United States of America. In 22nd of June 2009, United States issued an act called Family Smoking Prevention and Tobacco Control Act, where the Section 907(a)(1)(A) stated about the restriction against the selling of characterized flavors cigarettes but excluding menthol cigarettes from the restriction. As the biggest clove cigarettes exporter to the United States, Indonesia is suffering from a huge loss due to the implementation of the act. This study aims to analyze the clove cigarettes dispute resolution process between Indonesia and United States. By using Scenario Building method, the analysis indicates the four dispute resolution scenarios. The scenario with the condition of Indonesia won the dispute clove cigarettes is the best solution because the positive impact on the economy, social and politics, especially bilateral relations between Indonesia and the United States of America.